Facies and fauna of Triassic to Early Jurassic deposits from the Hochfelln Massif (Northern Calcareous Alps, Bavaria) - Seuß, Barbara; Nützel, Alexander; Höfling, Richard; Schulbert, Christian (System Earth - Biosphere Coupling, 2005)
A suite of Early Mesozoic (Late Triassic, Norian to Early Jurassic) calcareous beds was studied from the Hochfelln Massif in the Northern Calcareous Alps (Bavaria, South Germany). The main part of the Hochfelln Mountain is built up by the Hauptdolomit Group consisting of thick peritidal deposits and overlain by basin deposits of the Rhaetian Kössen Formation and Rhaetian reefoidal limestone with corals. Unlike many other sections in the Tethys realm, coral growth seems to continue into the Jurassic or starts again relatively early within the Early Jurassic. Silicified corals and other marine invertebrates are present in the calcareous, micritic Hochfelln Beds. A reexamination of previously collected ammonite material indicates the presence of Coroniceras sp. which suggests an Early Sinemurian age for the Hochfelln Beds (= Hochfellnkalk). Abundant sponge spicules (spiculites) suggest that sponges were the source for the silicification. The historical gastropod collection (Bayerische Staatssammlung für Paläontologie (BSP), Munich) from the Hochfelln Mountain was reexamined and new material was collected. The Hochfelln gastropod fauna yields a total of 28 species. It represents one of the richest Early Jurassic gastropod faunas of Germany and the Northern Calcareous Alps. The generic assignments of several species were changed and twelve species were newly reported some of which are undescribed. The relatively diverse Early Sinemurian gastropod fauna together with the coral growth on top of the Hochfelln Mountain indicate rapid recovery from the end-Triassic biotic crisi

Geowissenschaftliche Sammlungen - Höfling, Richard; Schulbert, Christian; Baier, Alfons (Die Sammlungen der Universität Erlangen-Nürnberg. Begleitband zur Ausstellung "Ausgepackt. Die Sammlungen der Universität Erlangen-Nürnberg" 20. Mai bis 29. Juli 2007, 2007)
UnivIS-Import:2015-04-20:Pub.2007.nat.dgeo.IGM.LAG.geowis

Triassic-Jurassic carbonates from the Hochfelln Mountain (Northern Calcareous Alps) - Its facies, silicified fauna and implications for the end-Triassic biotic crisis - Seuß, Barbara; Höfling, Richard; Nützel, Alexander (Facies, 2005)
A suite of Early Mesozoic (Late Triassic, Norian to Early Jurassic) calcareous beds was studied from the Hochfelln Mountain in the Northern Calcareous Alps (NCA, South Germany). The Hauptdolomit Group consists of thick peritidal deposits and is overlain by basin deposits of the Rhaetian Kössen Formation and Rhaetian reefoidal limestone with corals. Unlike many other sections in the Tethys realm, coral growth seems to continue into the Jurassic or starts again relatively early within the Early Jurassic. Silicified corals and other marine invertebrates are present in the calcareous, micritic Hochfelln Beds. A re-examination of previously collected ammonite material indicates the presence of Coroniceras sp. which suggests an Early Sinemurian age for the Hochfelln Beds. Abundant sponge spicules (spiculites) suggest that sponges were the source for the silicification. The site produced one of the most diverse Early Jurassic (Sinemurian) gastropod faunas of the NCA (25-30 species, some undescribed). The relatively diverse Early Sinemurian gastropod fauna and coral growth indicate rapid recovery from the end-Triassic biotic crisis. © Springer-Verlag 2005.
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.profes.triass
Keywords: Corals; End-Triassic mass extinction; Gastropods; Hochfelln; Northern Calcareous Alps; Silicification; Triassic/Jurassic transition